2020
DOI: 10.1021/acs.orglett.0c00442
|View full text |Cite
|
Sign up to set email alerts
|

Silyl Radical Mediated Cross-Electrophile Coupling of N-Acyl-imides with Alkyl Bromides under Photoredox/Nickel Dual Catalysis

Abstract: A photoredox Ni-catalyzed cross-coupling of N-acyl-imides with unactivated alkyl bromides has been developed that enables efficient access to a variety of functionalized alkyl ketones, including unsymmetrical dialkyl ketones, under very mild and operationally practical conditions. The reaction that operates without the need for any preformed carbon nucleophile proceeds via the combination of two different bond activation processes, i.e. Ni-catalyzed imide activation via C(acyl)-N bond cleavage, and (TMS)3Si ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…A related approach was developed by Li and co-workers 123 for the reductive acylation of acylimidazoles with aryl and alkyl bromides in the presence Zn as the reductant. Interestingly, Amgoune and coworkers 124 recently realized a nickel/photo dual catalyzed reductive cross-coupling of amides and alkyl bromides for the synthesis of alkyl ketones (Scheme 15c). The reaction proceeded well with various functionalities on the phenyl ring of the amides.…”
Section: Reductive Acylation and Carboxylation Reactionsmentioning
confidence: 99%
“…A related approach was developed by Li and co-workers 123 for the reductive acylation of acylimidazoles with aryl and alkyl bromides in the presence Zn as the reductant. Interestingly, Amgoune and coworkers 124 recently realized a nickel/photo dual catalyzed reductive cross-coupling of amides and alkyl bromides for the synthesis of alkyl ketones (Scheme 15c). The reaction proceeded well with various functionalities on the phenyl ring of the amides.…”
Section: Reductive Acylation and Carboxylation Reactionsmentioning
confidence: 99%
“…The process was designed to follow a radical relay pathway where a silyl radical is generated photocatalytically and serves as an abstracting agent to activate the alkyl bromide through homolytic C-Br bond cleavage (Scheme 1A). 10 Another exciting challenge that we subsequently considered was the design of an alternative strategy that would rely on the selective C(sp 3 )-H bond activation of simple alkanes through a radical hydrogen-atom transfer (HAT) process. 11,12 The groups of Doyle and Molander independently demonstrated that organohalides could serve as both coupling partners and sources of halide radicals that act as potent H-abstracting agents in Ni/photoredox cross-coupling reactions with aliphatic substrates.…”
Section: Published As Part Of the Cluster Modern Nickel-catalyzed Reactionsmentioning
confidence: 99%
“…This photoredox‐assisted reductive strategy has been quickly applied in nickel‐catalyzed C−C cross‐couplings between aryl and alkyl halides [13] . Strikingly, only one isolated example regarding ketones synthesis [14] was recently reported by Amgoune lab [13m] with using N ‐acyl‐imides as acyl donors (Scheme 1 A‐3). However, 3°‐radicals are still incompatible, which remains challenging in cross‐coupling reactions for the construction of quaternary carbon centers [13a,j, 15] …”
Section: Introductionmentioning
confidence: 99%